Grant Auditing in Focus: Perspectives of State Auditors and Beneficiaries on Efficiency and Challenges - Amra Gadžo; Anida Jagodić; Erna Delić (Belgrade Business and Arts Academy of Applied Studies; ZBW – Leibniz Information Centre for Economics, 2026)
This study analyses the significance, effects, and challenges of grant auditing in the public sector of the Federation of Bosnia and Herzegovina, focusing on identifying systemic weaknesses that limit the effectiveness of public fund management. Given that transfers account for 50–73% of the FBiH budget, their auditing represents a critical component of public financial oversight.The research employs a combination of quantitative and qualitative methods, integrating data from three sources: the views of state auditors (n=60), the views of audit subjects (n=100), and a systematic content analysis of audit reports for the period 2010–2023. Through seven research questions, the paper explores the significance of grant auditing, its impact on management efficiency and transparency, the frequency and types of irregularities, as well as the quality and feasibility of audit recommendations. Key findings reveal a paradoxical situation. While state auditors clearly recognise the strategic importance of grant auditing (M=4.40), and audit subjects assess audit recommendations as justified (M=4.03) and clear (M=4.03), there exists a substantial implementation gap. The feasibility of recommendations was rated considerably lower (M=3.37). The study identifies a cascading effect of systemic weaknesses that extends throughout the entire grant lifecycle, with the most critical areas being the complete absence of performance evaluation, unmeasurable allocation criteria, and inadequate supervision. Non-profit organisations were identified as the most vulnerable category of grant beneficiaries (M=3.87 vs. 2.85 for public enterprises). The most significant finding relates to the critical level of the accountability deficit. The lack of sanctions for managers (M=4.00) and political pressure from higher levels (M=3.73) were identified as key barriers to the implementation of recommendations, while workload was assessed as the least significant factor (M=2.73). This indicates that the problem is not technical (the quality of recommendations) or capacity-related (lack of time), but rather a fundamental issue of governance and political will. The study concludes that transformation is possible through holistic reforms that simultaneously address accountability mechanisms, systemic grant management procedures, institutional capacities, and protection against political interference.
Conference: The Fourth International Scientific and Professional Conference (BELECON 25), Belgrade, 6 June 2025
Keywords: M40; M41; M42; 330; Grant auditing; public sector accountability; audit recommendations; irregularities; compliance